PENGARUH KREATIVITAS DAN INOVASI TERHADAP KEWIRAUSAHAAN UMKM FOOD COURT - Eny Rochmatulaili; Suyanto Suyanto; Muhammad Alif Rahman (Yos Soedarso Economic Journal (YEJ), 2021)
From various aspects, the role of MSMEs in the national economy involves the government in formulating the Development Program in the National Medium Term Development Plan (RPJMN). The 2004-2009 RPJMN emphasizes a program to develop a business support system for MSMEs and a program for developing entrepreneurship and competitiveness. This concerns the formation of business behavior to achieve a more successful or successful performance and structure of micro, small and medium enterprises.According to Widayatun "Creativity is the ability to solve problems, which gives individuals creating original / adaptive ideas their full usefulness function to develop".Keywords: Creativity; UMKM; RPJMN.